Analysis Science Process Skills, Arnguing Ability and Digital Literacy of MAN 5 Batanghari Students Based on Gender Differences - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; Nirmala Prameswari* (Universitas Syiah Kuala, 2023)
Science process skills are skills that students must have in processing the scientific knowledge they have acquired. Both knowledge gained from the environment and digital media with literacy skills. So the ability to argue scientifically is needed to be able to convey information obtained scientifically so that it can solve problems in everyday life. Therefore, this study aims to analyze students' science process skills, argumentation skills, and digital literacy. The method used in this study is the explanatory mix method. The population in this study were students of MAN 5 Batanghari, while the sampling technique in this study used purposive sampling, namely students of class X IPA with a total of 35 students. The data collection instruments in this study were in the form of interview sheets, digital literacy questionnaires, and essay questions. Data analysis in this study used descriptive statistical methods. Gender-based SPS for students with dominant results (always good) is female. Then the ability to argue is also more in the female gender. Meanwhile, digital literacy that has the maximum value is male students